2015
DOI: 10.1039/c4ra08737b
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis and characterization of bio-organometallic compounds and their biological activity contour against human pathogens

Abstract: We have reported the synthesis of novel di & trisubstituted pyrroles and their biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The optimized reaction condition and reagents used for the synthesis of ( 3 ) and ( 5 ) shown in the Scheme were followed from our earlier reported work . The overall reaction comprises of two newly formed C‐C bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimized reaction condition and reagents used for the synthesis of ( 3 ) and ( 5 ) shown in the Scheme were followed from our earlier reported work . The overall reaction comprises of two newly formed C‐C bonds.…”
Section: Resultsmentioning
confidence: 99%
“…An efficient method to synthesize substituted pyrroles involving α‐aroylketene dithioacetals and p ‐toluenesulfonylmethyl isocyanide (TosMIC) with excellent yield has been demonstrated . In our earlier report, we found that di‐ and trisubstituted ferrocenoylpyrrole molecules had a good antibacterial activity but did not have an appreciable photophysical property. An attempt to improvise the same, we would like to introduce a chromophore in the pyrrole molecules to study their photophysical properties and its suitability toward the application in bio‐imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The novel di‐substituted pyrrole molecules 277 with ferrocene and aryl ring by the 1,3‐dipolar cycloaddition between α,β‐unsaturated carbonyl compounds 276 and tosylmethyl isocyanide (TosMIC) 263 a were prepared by Divakar et al [89] . The reaction proceeds smoothly under very mild conditions in the presence of sodium hydride in THF over 30 minutes in good yields (Scheme 92).…”
Section: Cycloaddition Reactionsmentioning
confidence: 99%
“…The (η 5 -Cp) 2 Fe has a 18 electrons closed shell, a remarkable stability at the air, especially in the solid state, and a reactivity similar to that of other aromatic species, that allowed extensive functionalization and the introduction of a huge number of substituents [1,2]. All these aspects favored the use of ferrocene and its derivatives in biological applications and in conjugation with biomolecules [3] and prompted the synthesis of compounds with potentiality as drugs [4].…”
Section: Introductionmentioning
confidence: 99%